Living up to the image of the ideal public leader: George Washington’s image in China - Wagner, Rudolf G. (The journal of transcultural studies, 2020)
Early Chinese biographies of George Washington were indirectly discussing the features a new kind of Chinese public leader might have to embody if he was to lead China out of its demise. Here was the promise of a colony of almighty England that had won its independence under Washington’s leadership, and had set up institutions that now made it into a quickly rising power that was respected by all. Candidates for the role of China’s Washington were well aware of such expectations, and tried to adjust their performance on the political stage down to dress, mien, and gait. This article traces the Chinese appropriation of George Washington to frame the image of a public leader in a post-Imperial China, from its beginning in the mid-nineteenth century to the foundation of the People’s Republic in 1949.